The Effect of Income Instability on Farmers' Consumption and Investment - Girao, J. A.; Tomek, W. G.; Mount, T. D. (The Review of Economics and Statistics, 1974)
POLICIES to promote price and income stability in agriculture have often been justified by the belief that stability would help farmers make better consumption and investment decisions. However, review of literature makes it abundantly clear that the consequences of instability are matters of debate among economists. For instance, Caine (1966, p. 16) believes that a main evil resulting from fluctuations in income is lowering of the level of capital expenditure. Others argue that farmers adapt to the exigencies of fluctuating income and that instability, per se, has little influence on consumption and investment (e.g., Campbell, 1964, p. 59).1 In this paper, consumption and investment functions are estimated for two groups of southern Minnesota farmers with contrasting degrees of income stability. Since various hypotheses exist about investment and consumption behavior, alternative models are outlined in the first section. Consequently, this paper provides empirical evidence for evaluating alternative models as well as assessing the effects of instability. The data and the estimation procedures are briefly described in the second section, and the empirical results are presented in the third.